Realization of Restorative Justice Resolution for Illegal Fishing Perpetrators in The Karimunjawa Conservation Area - Ariyani, Wiwit; Sajidah, Graha Salma Nafa; Utomo, Aldi Priyo; Tara, Erlinda Dwi; Assakhiy, Herfiana Putri; Fahmi, Mujab; Azlina, Nor (Program Studi Hukum Keluarga Islam, 2024)
Resolving illegal fishing through penalties does not necessarily result in justice for the parties. Theoretically, legal experts state that there are weaknesses in resolving cases using penalty measures. The typology of this research is sociological juridical. The data source comes from the primary data and is supported by secondary data consisting of primary, secondary and tertiary legal materials. The data collection method was carried out using directed interviews with sources and literature study. Data processing and analysis was carried out qualitatively using inductive methods. The urgency of using restorative justice in resolving illegal fishing is to minimize the weaknesses of penalty efforts which emphasize the element of retaliation solely for mistakes that have been made by providing suffering so that the perpetrator will repent. The concept of restorative justice places greater emphasis on restoring damage to be repaired by the perpetrator based on the agreement of the parties. Apart from that, it will also be able to lower the accumulation of cases in law enforcement agencies so that it will also reduce the overcapacity of correctional institutions which become a problem in Indonesia. The model for resolving illegal fishing using restorative justice in the Karimunjawa conservation area can be implemented with the criteria that the perpetrator is a local resident of Karimunjawa whose citizenship is an Indonesian and the losses incurred are not too large, both in terms of the number of fish and in terms of environmental damage and this is the first time this criminal act has been committed.